All Days 2010
DOI: 10.2118/136916-ms
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Methods for Reservoir Life-Cycle Optimization and Well Placement

Abstract: Several simple examples are presented that demonstrate the application of an ensemble-based method to production optimization. In particular, some practical aspects of the method such as ensemble size, perturbation, regularization and smoothing, and robust gradient estimation are discussed by comparison with an adjoint approach. The controls in the presented examples are inflow control valve settings for fixed time intervals or well position. We find that the performance of the method is clearly affected by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…is no longer valid. However, one can still obtain an approximation of C U ∇ J E ( u ℓ ) by first using a simplex gradient to approximate ∇ J E ( u ℓ ) and then multiplying this gradient by C U . For information on the simplex gradient formulation in general see, for example, .…”
Section: Comments On Stochastic Simplex Approximate Gradientmentioning
confidence: 99%
See 1 more Smart Citation
“…is no longer valid. However, one can still obtain an approximation of C U ∇ J E ( u ℓ ) by first using a simplex gradient to approximate ∇ J E ( u ℓ ) and then multiplying this gradient by C U . For information on the simplex gradient formulation in general see, for example, .…”
Section: Comments On Stochastic Simplex Approximate Gradientmentioning
confidence: 99%
“…and the definitions of Eqs. and , it easily follows that for each k , k = 1,2,⋯ N e , j=1Np(û,j,ku)(J(mk,û,j,k)J(mk,u))=ΔÛ,k(Δj,k)ΔÛ,k(ΔÛ,k)TuJ(mk,u). Thus, as in , an approximate stochastic gradient, denoted by ∇ u ,sto J ( m k , u ℓ ), is given by boldu,stoJ(boldmk,boldu)=()normalΔtrueboldÛ,k(normalΔtrueboldÛ,k)T+normalΔtrueboldÛ,k(normalΔboldj,k)bolduJ(boldmk,boldu…”
Section: Comments On Stochastic Simplex Approximate Gradientmentioning
confidence: 99%
“…In an ideal case we would like to additionally meet such short-term economic objectives whilst still maintaining the life cycle objectives. Thus we choose a secondary 10 Undiscounted NPV ($)…”
Section: Objective Functionsmentioning
confidence: 99%
“…The control samples are drawn from a multivariate Gaussian distribution with a user-defined (constant) covariance matrix and a known mean. Several publications (Chen 2008;Chen and Oliver 2012;Leeuwenburgh et al 2010;Su and Oliver 2010) have shown that EnOpt can achieve good results of practical value on a variety of different reservoir models and recovery techniques. A major drawback, however, is the significantly lower computational efficiency and accuracy compared to the adjoint method.…”
Section: Introductionmentioning
confidence: 99%